f ( x

)
y

3

lim f ( x )

2

x →0

1

x
−4

−3

−2

−1

1

2

3

4

5

−1

−2

−3

lim+ f ( x )

y

3

x →0

2

1

x
−4

−3

−2

−1

1

2

−1

−2

limπ sin x
−3

x→

2

3

4

5

limcos x
x →0

y

3

2

1

x

lim− f ( x )

x →−1

−4

−3

−2

−1

1

−1

−2

−3

2

3

4

5

lim e
x →0

x

y

3

2

1

x

−4

lim f ( x )
x →0

−3

−2

−1

1

−1

−2

−3

2

3

4

5

lim f ( x )
x →0

y

3

2

1

x

−4

−3

−2

−1

1

2

3

−1

−2

−3

lim cos x

x → 2π

4

5

lim f ( x )

y

3

x →1

2

1

x

−4

−3

−2

−1

1

−1

−2

−3

2

3

4

5

y

lim f ( x )

3

2

x →0

1

x

−4

−3

−2

−1

1

2

3

4

5

−1

−2

−3

lim f ( x )

y

3

x →0

2

1

x

−4

−3

−2

−1

1

−1

−2

−3

2

3

4

5

Master your semester with Scribd & The New York Times

Special offer for students: Only $4.99/month.

Master your semester with Scribd & The New York Times

Cancel anytime.